An Efficient and High-Speed Overlap-Free Karatsuba-Based Finite-Field Multiplier for FGPA Implementation - Heidarpur, Moslem; Mirhassani, Mitra (IEEE transactions on very large scale integration (VLSI) systems, 2021)
Cryptography systems have become inseparable parts of almost every communication device. Among cryptography algorithms, public-key cryptography, and in particular elliptic curve cryptography (ECC), has become the most dominant protocol at this time. In ECC systems, polynomial multiplication is considered to be the most slow and area consuming operation. This article proposes a novel hardware architecture for efficient field-programmable gate array (FPGA) implementation of Finite-field multipliers for ECC. Proposed hardware was implemented on different FPGA devices for various operand sizes, and performance parameters were determined. Comparing to state-of-the-art works, the proposed method resulted in a lower combinational delay and area-delay product indicating the efficiency of design.